Influence of ICTs on organizational competitiveness (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2017)
The purpose of the research was to diagnose the influence of ICT on organizational competitiveness, for which 14 public education institutions in the 7th and 8th districts of the municipality of San José de Cúcuta were taken as a reference, seeking to know how the technological component influences the strengthening of the educational service and in turn in the development of cognitive skills in students to be competent, with the purpose that the institutions of the studied sector conceive these tools as a foundation for a quality education, stimulating the active participation of the student in the search for a desirable and significant self-learning in order to achieve a successful insertion in higher education. The theoretical bases that supported the objectives of the study were the school dimension of the Institute for Educational Development and Innovation of the OEI (2009), the instrumental competence by Escamilla (2008) and the business competitiveness factors by Martínez, Santero, Sánchez & Marcos (2009). The study was developed in the descriptive framework with a cross-sectional quantitative approach, method (M.A.S) where the survey technique was used for three samples composed of 14 rectors, 103 teachers and 303 students of the communes mentioned. It was concluded that being the use of ICT influential in organizational competitiveness, in the analyzed institutions it is evidenced as a positive factor.
Keywords: ICT; competitiveness; education; cognitive skills; communes